Cross-species transmission, evolution and zoonotic potential of coronaviruses - Li, Qian; Shah, Taif; Wang, Binghui; Qu, Linyu; Wang, Rui; Hou, Yutong; Baloch, Zulqarnain; Xia, Xueshan (Frontiers in Cellular and Infection Microbiology, 2023)
Coronaviruses (CoVs) always evolve, crossing species barriers and spreading across host ranges. Over the last two decades, several CoVs (SARS, MERS, and SARS-CoV-2) have emerged in animals and humans, causing significant economic losses. In addition, new CoVs have been identified in captive wildlife, raising global conservation concerns. Because frequent cross-species transmission facilitates the evolution and emergence of novel CoVs, it is critical to determine their potential emerging source and the circumstances under which this transmission occurs in order to slow disease emergence. In this review, we use genetic and ecological data to disentangle the evolution of various CoVs in wildlife, humans, and domestic mammals. We thoroughly investigate several host species and outline the epidemiology of CoVs toward specific hosts. We also discuss the cross-species transmission of CoVs at the interface of wild birds, mammals, humans, and animals. Clarifying the epidemiology and diversity of species reservoirs will significantly impact our ability to respond to the future emergence of CoVs in humans and domestic animals.